Morphology and agglomeration control of LiMnPO4 micro- and nanocrystals - Neef, Christoph; Jähne, Carsten; Meyer, Hans-Peter; Klingeler, Rüdiger (Langmuir, 2013)
Microwave-assisted hydrothermal synthesis was used to grow LiMnPO4 micro- and nanocrystals from acetate precursors. By appropriate adjustment of the precursor concentration and the pH-value of the reactant, the product composition and purity along with the crystal size can be manipulated, resulting in particle-dimensions from around 10 μm down to a few 100 nm. Prisms and plates with hexagonal basal faces as well as cuboid and rod-like particles were produced. The effects on the crystal morphology as well as on the materials texture and agglomeration tendency are discussed and a comprehensive agglomeration phase diagram is constructed.
Im Titel ist die Zahl "4" tiefgestellt
Gesehen am 08.12.2021